Ответы и объяснения

2012-05-12T21:18:24+04:00

5х+у=-3

х^2+5ху-8х+5у=-15

 

5х-3=у

х^2+5x(5x-3)-8x+5(5x-3)=-15

x^2+25x^2-15x-8x+25x-15+15=0

26x^2+2x=0

x(26x+2)=0

x=0 ИЛИ 26x+2=0

              x=-1/13

 

x=0

5х-3=у

 

y=-3

x=0

 

 

x=-1/13

5х-3=у

 

y=-3 и 5/13

x=-1/13

жирным шрифтом выделен ответ

 

Лучший Ответ!
2012-05-12T21:28:41+04:00

5х+у=-3                          у=-3-5х                                        у=-3-5х            у=-3-5х

х^2+5ху-8х+5у=-15         х²+5х(-3-5х)-8х+5(-3-5х)=-15       -24х²-48х=0     -х(24х+48)=0

 

у=-3-5х    у₁=-3         у=-3-5х   у₂=7

х₁=0         х₁=0         х₂=-2      х₂=-2 ОТВЕТ(0;-3) и (-2;7)